Three-Dimensional Numerical Study on the Efficiency Droop in InGaN/GaN Light-Emitting Diodes - Quoc-Hung Pham; Jyh-Chen Chen; Huy-Bich Nguyen (IEEE Photonics Journal)
The efficiency droop characteristics of single quantum well (SQW) InGaN/GaN light-emitting diodes (LEDs) including the phase-space filling (PSF) effect are predicted by a three-dimensional (3-D) numerical simulation. The carrier transport is based on the solution of the 3-D non-linear Poisson and drift-diffusion equations for both holes and electrons. A modified formulation of the Shockley—Reed–Hall (SRH) coefficient is proposed to describe the SRH carrier lifetime behavior, which increases at a low excitation level and decreases at a higher one. The current crowding causes a non-uniform distribution of the carrier concentration in the active layer that leads to the inversion of the local internal quantum efficiency (IQE) under the n-pad region when the injection current density increases from low to high levels. To further understand the correlation of the efficiency droop with the PSF effect, we systematically investigate carrier transport in the SQW InGaN/GaN LEDs and how the different PSF effect coefficients affect the current–voltage curve and IQE. The lumped IQE found in this study agrees well with previous experimental measurements. Moreover, the PSF effect has a strong impact on the IQE behavior including its peak and droop in efficiency.